The Presidency and the Executive Branch in Latin America: What We Know and What We Need to Know - Alejandro Bonvecchi; Carlos Scartascini (Inter-American Development Bank (IDB), 2011)
The presidential politics literature depicts presidents either as all-powerful actors or figureheads and seeks to explain outcomes accordingly. The president and the executive branch are nonetheless usually treated as black boxes, particularly in developing countries, even though the presidency has evolved into an extremely complex branch of government. While these developments have been studied in the United States, far less is known in other countries, particularly in Latin America, where presidential systems have been considered the source of all goods and evils. To help close the knowledge gap and explore differences in policymaking characteristics not only between Latin America and the US but also across Latin American countries, this paper summarizes the vast literature on the organization and resources of the Executive Branch in the Americas and sets a research agenda for the study of Latin American presidencies.
Keywords: D73; D78; H00; 330